Suicide in South Asia: a narrative review - Joshi, Devavrat; Regmi, Sushant; Sharma, Pawan (Journal of Patan Academy of Health Sciences, 2024)
Suicide is a major public health issue globally as well as in the South Asian region. The figures of suicide death are compelling but the attention this issue receives is relatively less in this region. The epidemiologic characteristics and recent trends in suicide in South Asia reflects specific sociocultural situations and economic transitions in the region. The challenges in getting an exact magnitude, cultural influences, religious sanctions, stigmatization and socio-economic factors are the major dimensions that this problem needs to be looked into. Though there have been efforts on decreasing suicide rates, most of them are uncoordinated, underresourced, and generally unevaluated. In this narrative review we aim to present the different dimensions and challenges of suicide prevention in South Asian context and provide few recommendations that would be helpful in suicide prevention.